PENGARUH KOMITMEN ORGANISASI, PERILAKU KEWARGAAN ORGANISASIONAL, DAN ETIKA KERJA ISLAMI TERHADAP PERUBAHAN ORGANISASI (Studi terhadap Dosen Perguruan Tinggi Swasta di Surakarta) - Almaidah, Siti (Riset Manajemen & Akuntansi, 2014)
The purpose of this study was to examine the influence of organizational commitment, organizational citizenship behavior, and Islamic work ethics to organizational change on Private Higher Education Lecturer in Surakarta. The development and rapid changes currently requires universities to adjust to the changes that occur, and must be actively making changes internally, arrangement, and organization development, and responsive to external factors. The study population is a lecturer at private universities in Surakarta and a Muslim. Samples taken were 100 respondents. The sampling technique was conducted using purposive sampling. Based on the test results it can be concluded that, organizational commitment, organizational citizenship behavior, and Islamic work ethic, have a significant impact on organizational change.